PENGARUH FASILITAS KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. BANK RIAUKEPRI CABANG TELUK KUANTAN KABUPATEN KUANTAN SINGINGI - Apri Dahlius; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is conducted at PT. Bank Riaukepri Branch Teluk Kuantan Sub-Province Kuantan Singingi, as for intention of this research is to know influence of facility work to satisfaction of employees activity of PT. Bank Riaukepri Branch Teluk Kuantan Sub-Province Kuantan Singingi. Facility work as independent variable (X). Meanwhile satisfaction of activity as dependen variable (Y). Problem of this research is facility office making employees less satisfied in working in among others is network of internet which often there is trouble, availibility of limited office tranportasi. Later then place park specially of employees do not be provided so that vehicle of employees parking in place park client. While building still adequate enough, this matter because of PT. Bank Riaukepri Branch Teluk Kuantan Sub-Province Kuantan Singingi not yet owned building alone and in this time still rent two shop house building. Population and of sampel research taken by counted 32 responder. Date obtained from result of quetioner and here in after processed to later then tested with statistic through program of SPSS. Result of obtained calculation that activity facility have an effect on positive to satisfaction of employees activity of PT. Bank Riaukepri Branch Teluk Kuantan Sub-Province Kuantan Singingi equal to 96,5%.